Modal properties variation and collapse assessment of masonry arch bridges under scour action. (15th November 2019) - Scozzese, Fabrizio; Ragni, Laura; Tubaldi, Enrico; Gara, Fabrizio
Highlights: Numerical simulations of flood-induced scour around the piers of masonry bridges. Failure mechanism simulation of an Italian bridge after the flood of December 2013. Operational Modal Analysis (OMA) of the remaining half part of the bridge. Bridge's modal properties sensitivity to different scour levels. Abstract: This paper investigates the problem of flood-induced scour on masonry arch bridges through the analysis of a real case study, Rubbianello Bridge. This is a multi-span masonry arch bridge located in Central Italy, which suffered the collapse of two of the seven spans due to foundation scour during a severe flood in December 2013. The study has a twofold aim: to evaluate with a numerical model the level of scour which led to the bridge failure in 2013 and the corresponding collapse mechanism, and to assess the sensitivity of the bridge's modal properties (vibration frequencies and mode shapes) to different levels of scour. An accurate nonlinear three-dimensional model of the bridge is developed, whose elastic properties are calibrated to match the results of dynamic identification tests performed via Operational Modal Analysis (OMA) on the remaining portion of the bridge. A numerical simulation of the effects of the scour hole progression is also performed on the full bridge, according to recently proposed techniques. The study results provide useful insights on both the cause of collapse of the bridge and the suitability of OMA for bridge scour monitoring.